The Role of Islamic Religious Education in Resolving Legal Conflicts Between Teachers and Students at MTs Darul Ihsan Hamparan Perak: A Perspective of the Child Protection Law - Ismi Fauziah; Syahrul Sitorus; Nona Kumala Sari; Khairuddin YM; Atika Ridvi Amelia Nasution (The Islamic Education and Multiculturalism Foundation, 2024)
This study aims to explore the role of Islamic Religious Education (PAI) in resolving legal conflicts between teachers and students at MTs Darul Ihsan Hamparan Perak, particularly within the framework of the Child Protection Law No. 35 of 2014. Utilizing a descriptive qualitative approach through interviews, observations, and documentation, the study reveals that PAI plays a significant role in conflict resolution by instilling religious values such as consultation, compassion, and justice. PAI teachers act as mediators, promoting dialogue and education while adhering to child protection principles by avoiding physical or psychological violence and favoring persuasive approaches. Challenges include a lack of parental understanding regarding discipline based on religious values, addressed through socialization and education. This study emphasizes that synergy between PAI and the Child Protection Law can serve as an effective model for resolving legal conflicts in educational settings.